Differential expression of antiviral and immune-related genes in individuals with COVID-19 asymptomatic or with mild symptoms - Gajate-Arenas, Malena; García-Pérez, Omar; Chao-Pellicer, Javier; Domínguez-De-Barros, Angélica; Dorta-Guerra, Roberto; Lorenzo-Morales, Jacob; Córdoba-Lanus, Elizabeth (Frontiers in Cellular and Infection Microbiology, 2023)
COVID-19 is characterized by a wide range of symptoms where the genetic background plays a key role in SARS-CoV-2 infection. In this study, the relative expression of IRF9, CCL5, IFI6, TGFB1, IL1B, OAS1, and TFRC genes (related to immunity and antiviral activity) was analyzed in upper airway samples from 127 individuals (97 COVID-19 positive and 30 controls) by using a two-step RT-PCR. All genes excepting IL1B (p=0.878) showed a significantly higher expression (p<0.005) in COVID-19 cases than in the samples from the control group suggesting that in asymptomatic-mild cases antiviral and immune system cells recruitment gene expression is being promoted. Moreover, IFI6 (p=0.002) and OAS1 (p=0.044) were upregulated in cases with high viral loads, which could be related to protection against severe forms of this viral infection. In addition, a higher frequency (68.7%) of individuals infected with the Omicron variant presented higher viral load values of infection when compared to individuals infected with other variants (p<0.001). Furthermore, an increased expression of IRF9 (p<0.001), IFI6 (p<0.001), OAS1 (p=0.011), CCL5, (p=0.003) and TGFB1 (p<0.001) genes was observed in individuals infected with SARS-CoV-2 wildtype virus, which might be due to immune response evasion of the viral variants and/or vaccination. The obtained results indicate a protective role of IFI6, OAS1 and IRF9 in asymptomatic -mild cases of SARS-CoV-2 infection while the role of TGFB1 and CCL5 in the pathogenesis of the disease is still unclear. The importance of studying the dysregulation of immune genes in relation to the infective variant is stand out in this study.